ASPECTS OF THE BOUNDARY ELEMENT METHOD APPLICATION FOR PREDICTING RELIABILITY OF HIGH-RISE STRUCTURES - Morgun, Alla; Shvets, Anna; Shevchenko, Oleksiy (Scientific Works of Vinnytsia National Technical University, 2015)
The paper deals with theoretical substantiation of the foundation engineering nonlinear problem, which requires application of reliability and plasticity theories, computer processing. Plasticity consideration makes it possible to increase bearing capacity of the foundation construction. REFERENCES 1. Определяющие законы механики грунтов / [под ред. В. Н. Николаевского, ред. серии А. Ю. Ишлинский, Г. Г. Черный]. – М. : Мир, 1975. – 231 с. 2. Бойко І. П. Напружено-деформований стан ґрунтового масиву при побудові нових фундаментів поблизу існуючих будинків / І. П. Бойко, О. В. Сахаров // Основи і фундаменти: Міжвідомчий науково-технічний збірник. – 2004. – Вип. 28. – С. 3 – 10. 3. Моргун А. С. Метод граничних елементів в розрахунках несучої спроможності кільцевих та круглих в плані фундаментних конструкцій / А. С. Моргун, О. В. Франчук // Вісник ВПІ. – 2012. – № 5. – С. 11 – 14. 4. Бреббия К. Методы граничных елементов / К. Бреббия, Ж. Теллес, Л. Вроубел. – М. : Мир, 1987. – 525 с. 5. Голубков В. Н. Исследование процесса формирования зоны деформации в основаниях одиночных свай / В. Н. Голубков, Ю. Ф. Тугаенко, Б. О. Хуторянский // Основания и фундаменты: Республиканский межведомственный научно-технический сборник. – 1971. – Вып. 4. – С. 9 – 13.